ANALISIS WACANA RETORIKA DAKWAH K.H. MUHAMMAD ARIFIN ILHAM DAN K.H. YUSUF MANSUR - Bahroni Bahroni (IAIN Salatiga, 2018)
Da’wah has become a very strategic object. Thus, the involvement of mass media playsimportant role in the activities, both printed and electronic. There are many well-knownDa’i in Indonesia that have strong influence to the communities such as K.H. Muhammad Arifin Ilham (MAI). The study aims to demonstrate the grammatical structure and lexical cohesion of MAI’s da’wah rhetoric. The data analysis consists of: (1) sorting the data based on the problem; (2) formulating the data units into each sequence in accordance with the possibility of their features; (3) interpreting the data values based on the problem; (4)evaluating the level of visibility and completeness of the data that linked to the range of problems. The structure of the grammatical ohesion of MAI’s rhetoric includes reference, substitution, ellipsis and conjunction. The manifestation of MAI’s lexical cohesion rhetoric comprises of repetition, synonym, antonym, hyponym, collocation, and equivalence. AbstrakDakwah merupakan hal yang sangat strategis. Oleh karena itu, aktivitas tersebut tidak luput dari liputan media massa, baik cetak maupun eletronik. Di antara da’i Indonesia yang sangat dikenal oleh masyarakat luas adalah K.H. Muhammad Arifin Ilham (MAI) dan K.H. Yusuf Mansur (YM). Tujuan penelitian ini untuk mendeskripsikan wujud kohesi gramatikal dan leksikal retorika dakwah MAI dan YM. Adapun langkah analisis datanya sebagai berikut: (1) pengurutan data sesuai dengan masalahnya; (2) pembentukan satuan-satuan data dalam setiap urutannya sesuai dengan kemungkinan hubungan ciri kategorinya; (3) interpretasi nilai data sesuai dengan masalahnya; (4) evaluasi tingkat kelayaan dan kelengkapan data dikaitkan dengan rentang masalahnya. Wujud kohesi gramatikal retorika dakwah MAI dan YM mencakup referensi, substitusi, elipsis, dan konjungsi. Wujud kohesi leksikal retorika dakwah MAI dan YM mencakup repetisi, sinonimi, antonimi, hiponimi, kolokasi, dan ekuivalensi.